Villains are destined to die. 1 - Suol; Gwon, Gyeoeul (Ize Press, 2022)
"In the Easy Mode of Daughter of the Duke Love Project!, you play as Ivonne, the duke's long-lost daughter who quickly gains the affection of the various male characters to win the game. Very easy! In Hard Mode, you play as "villainess" Penelope Eckhart, the duke's fake daughter who starts her adventure with negative affection points. Very hard...and filled with gruesome deaths?! Misunderstood and pining for love, one girl finds that she has much in common with Penelope and tries again and again to get her "good ending." She is granted one more try...when she falls asleep and wakes up as Penelope herself in the hostile world of the game!"--